On Using ANT for Studying Information Systems: A (Somewhat) Socratic Dialogue - Latour, Bruno (Sociologija. Mintis ir veiksmas, 2020)
It is the Lithuanian translation of the article written by Bruno Latour. In this article in the form of a dialogue between professor and doctoral student B. Latour explains the main principles of the Actor-Network-Theory, his approach to structural analysis, reflexivity, agency and social sciences. For the first time, this article was published in 2004 in a book edited by C. Avgerou, C. Ciborra, F. F. Land ‘The Social Study of Information and Communication Technology. Innovation, Actors, and Contexts’ (Oxford University Press).
Keywords: none